Language regard : methods, variation, and change - Evans, Betsy; Benson, Erica J.; Stanford, James N.
"Bringing together a team of renowned international scholars, this volume provides a wide-ranging collection of historical and state-of-the-art perspectives on language regard, particularly in the context of language variation and language change, and importantly, highlights the range of new methodologies being used by linguists to explore and evaluate it. The importance of language regard to the inquiry of language variation and change in the field of sociolinguistics is increasingly being recognized, yet misunderstandings about its nature and importance continue to exist. This volume provides scholars and students of sociolinguistics, with the tools and theory to pursue such inquiry. Contributions and research come from Europe, North America, and Asia, and language varieties such as Spanish, Dutch, Danish, and American Sign Language are discussed"--